You are on page 1of 14

# Lecture 2

1 Osculating/rectifying/normal
plane to a curve
Defn: The osculating plane at α(0) is the plane
spanned by T(0) and N(0)
The rectifying plane is the plane spanned by
T(0) and B(0)
The normal plane is the plane spanned by N(0)
and B(0)
The osculating plane comes closest to contain-
ing the curve α near α(0).
The normal plane is the plane perpendicular
to α at α(0).

2 Involute, evolute
Defn: The iinvolute of a curve α is the curve β
for which

## 2. the tangent vectors to α and β at α(t) and

β(t) (resp.) are perpendicular.
1. β(t) is then called the involute of α(t). α is
called an evolute of β. (There is more than
one evolute of β, but the involute of α is
unique.)
2. The involute can be characterized as
β(s) = α(s) + (c − s)T(s)
for some constant c.
3. If you wrap a string around the curve α
starting at s = 0, the involute β(s) is the
path the end of the string follows as you un-
wrap it, always pulling the string taut.
Proposition If β is arclength parametrized, then
1
α(s) = β(s) + N(s)
κ(s)

## 3 Curves are clssified by cur-

vature and torsion
Defn: A space curve is a curve in R3 which is not
a plane curve.
Defn: A rigid motion is a composition of transla-
tions and rotations. In other words F (x) = Ax+B
for a linear transformation A with det(A) > 0.
Theorem: Two curves C and D with nonzero
curvatures are congruent iff there is a rigid motion
F such that F (C) = D.
Proof:
(→)
Suppose F (C) = D for some rigid motion F
(F as above). Then D(s) = Aα(s)+B. So D′ (s) =
AC ′ (s). So |D′ (s)| = 1 because |C ′ (s)| = 1. Then
D is also arclength parametrized and T(D) = AT)C).
We differentiate once more to get κ(D)N(D)(s) =
κ(C)AN(s).
AN is a unit vector.
So since N(D) = AN(C), we have κ(D) =
κ(C).
But B(D) = T(D)xN(D) = A(T(C)×N(s)) =
AB(s) .
Finally B(D) = −τ N(D) and B′ (D) = AB′ (s) =
−τ (s)AN(s) = −τ (s)N(D)(s).
Hence τ (D) = τ (C) as we wanted to prove.
(←)
Suppose κ(C) = κ(D) and τ (C) = τ (D). We
define a rigid moton F as follows. Let A be the
unique orthogonal matrix so that AT(C) = T(D)
and similarly for N and B. Then det(A) = 1 .
Let B = D(0) − AC(0).
Set R(s) = AC(s).
Claim R(s) = D(s).
By the argument in the first part of the proof,
κ(D) = κ(AC) = κ(C) and similarly for τ .
Let

f (s) = T(AC)(s)·T(D)(s)+N(AC)(s)·N(D)(s)+B(AC

## We differentiate f using the Frenet formulas

for T ′ , N ′ and B ′ .
This gives an expression that is 0 since there
are terms in κ(s) which cancel, and terms in τ (s)
also cancel.
So we have f (0) = 3 (we chose f that way), so
f (s) = 3 for all s.
Since each of the dot products (between unit
vectors) must be ≤ 1, the sum can only be 3 if all
terms are 1 for all s. This implies equality of the
T , (as well as the N and the B). 
Example: A circular helix has constant κ and
constant τ . It follows from the Theorem that this
is the only curve that has constant κ and τ .
4 Isoperimetric inequality
Defn: A closed curve is simple if it does not in-
tersect itself.
The isoperimetric inequality maintains that if
γ is a simple closed curve with length L and en-
closing an area A, then

A ≤ L2 /(4π).

## Proof: WLOG assume L = 2π (since rescaling

by r changes A by r2 and changes L by r, so it
does not affect the claim.
Assume γ is parametrized by arclength.
Let x(s) and y(s) be the coordinate functions
of γ. Because the curve is closed, x and y can be
expanded as a Fourier series:
X
x(s) = an eins
n∈Z

X
y(s) = bn eins
n∈Z

## x′ (s) = sumn∈Z inbn eins

Since x and y are real-valued, x2 = |x|2 so by
Parseval’s identity
Z 2π X
1
|x′ (s)|2 ds = |nan |2 .
2π 0
n∈Z

## According to the arc length formula,

Z 2π
L= |γ ′ (s)|ds.
0

Since
γ ′ (s)|2 = |γ ′ (s)| = 1
(because γ is arclength parametrized) we have
Z 2π
2π = L = (|x′ (s)|2 + |y ′ (s)|2 )ds.
0

So X
n2 (|an |2 + |bn |2 ) = 1.
n∈Z

## According to Green’s theorem,

Z Z 2π
1
A = (xdy−ydx) = (x(s)y ′ (s)−y(s)x′ (s))ds.
γ 2 0
Recall that the inner product of f and g is defined
as Z 2π
f (s)ḡ(s)ds.
0
Using the Fourier series of the real-valued
R 2π insfunc-
tions x(s) and y(s), and recalling that 0 e eims ds =
0 unless n = −m, we have that
X
A=π n(an b¯n − bn a¯n .
n∈Z

Now use

## |an b¯n − bn a¯n | ≤ 2|an ||bn | ≤ |an |2 + |bn |2 .

It follows that
A X X X
=| n(an b¯n −bn a¯n |≤ |n|(|an |2 +|bn |2 ) ≤ n2
π
n∈Z n∈Z n∈Z

Hence A ≤ π. 
Because |n| < n2 when |n| > 1 we may con-
clude that the only curve for which A = L2 /(4π).